The French Observational Cohort of Usual Smokers (FOCUS) cohort: French smokers perceptions and attitudes towards smoking cessation - Solesse Anne; Jeanpetit Yasmine; Vicaut Eric; Stoebner-Delbarre Anne; Peiffer Gérard; Aubin Henri-Jean; Bonnelye Geneviève; Thomas Daniel (BMC, 2010)
Abstract Background Despite increasing governmental anti-smoking measures, smoking prevalence remains at a high level in France. Methods The objectives of this panel study were (1) to estimate smoking prevalence in France, (2) to identify smokers' profiles according to their perceptions, attitudes and behaviour in relation to smoking cessation, (3) to determine predictive factors of quit attempts, and (4) to assess tobacco-related behaviours and their evolutions according to the changes in the smokers' environments. A representative sample of French population was defined using the quota method. The identified cohort of smokers was assessed, in terms of smoking behaviour, previous quit attempts, and intention to quit smoking. Results A response rate of 66% for the screening enabled to identify a representative sample of the French population (N = 3 889) comprising 809 current smokers (21%). A majority of current smokers (63%) had made an attempt to quit smoking. Main reasons for having made the last attempt were cost (44%), social pressure (39%), wish to improve physical fitness (36%), fear of a future smoking-related disease (24%), and weariness of smoking (21%). Few attempts (16%) were encouraged by a physician. In those who used some kind of support (38%), NRT was the mostly used. Relapse was triggered by craving (45%), anxiety/stress (34%), a significant life event (21), weight gain (18%), and irritability (16%). Depression was rarely quoted (5%). Forty percent of smokers declared they intended to quit smoking permanently. Main reasons were cost (65%), physical fitness improvement (53%), fear of a future smoking-related disease (43%), weariness of tobacco (34%), and social pressure (30%). Using a smoking cessation treatment was considered by 43% of smokers that intended to quit. Barriers to smoking cessation were mainly fear of increased stress (62%), irritability (51%), and anxiety (42%), enjoying smoking (41%), and weight concerns (33%). Conclusion Smoking prevalence and smoking cessation attempts rate were lower in this survey than in previous reports. Cost and social pressure were the main reasons for quitting smoking, maybe an effect of dramatic tax increases and smoking ban.